ENHANCING STUDENTS' ARGUMENTATIVE WRITING THROUGH PROBLEM-BASED LEARNING AND CRITICAL THINKING SKILLS - Yamin, Moh (University of Kuningan, 2025)
This study aims to investigate whether the students who are treated using problem-based learning (PBL) with critical thinking have better writing ability than the students who are treated not using problem-based learning (PBL) with critical thinking. The research design was quasi experimental. Solomon Three-Group Design was used because there were three groups conducted in this study to minimize the intervening variables that might affect the result of the study. MANCOVA was used for data analysis. The study result says that problem-based learning (PBL) with critical thinking taught to the students was effective to increase students’ writing ability. Their argumentative essay writings perform better in introduction (sig=0.00), main points (sig=0.01), critical thinking (sig=0.01), organization of (sig=0.03), style (sig=0.004), and mechanics (sig=0.03). This research is useful and meaningful for the teachers to use problem-based learning with critical thinking in teaching argumentative essay. For the next researchers who will research the relevant topic, this study result can be used for enriching their knowledge for researching argumentative essay, comparison and contrast essay, expository essay.